Miocene pollen and spore flora of Eniwetok Atoll, Marshall Islands - Leopold, Estella B. (Bikini and nearby atolls, Marshall Islands., 1969)
"A Miocene pollen and spore flora representing raised island, intertidal, and beach-ridge environments is described from depths of 670 to 2,500 feet beneath Eniwetok Atoll."